Impaired Autophagy in Hilar Mossy Cells of the Dentate Gyrus and Its Implication in Schizophrenia. Issue 1 (20th January 2015) - Yuan, Yefeng; Wang, Hao; Wei, Zongbo; Li, Wei
Abstract Schizophrenia (SCZ) is a complex disease that has been regarded as a neurodevelopmental, synaptic or epigenetic disorder. Here we provide evidence that neurodegeneration is implicated in SCZ. The DTNBP1 (dystrobrevin-binding protein 1) gene encodes dysbindin-1 and is a leading susceptibility gene of SCZ. We previously reported that the dysbindin-1C isoform regulates the survival of the hilar glutamatergic mossy cells in the dentate gyrus, which controls the adult hippocampal neurogenesis. However, the underlying mechanism of hilar mossy cell loss in the dysbindin-1-deficient sandy (sdy) mice (a mouse model of SCZ) is unknown. In this study, we did not observe the apoptotic signals in the hilar mossy cells of the sdy mice by using the TUNEL assay and immunostaining of cleaved caspase-3 or necdin, a dysbindin-1- and p53-interacting protein required for neuronal survival. However, we found that the steady-state level of LC3-II, a marker of autophagosomes, was decreased in the hippocampal formation in the mice lacking dysbindin-1C. Furthermore, we observed a significant reduction of the cytosolic LC3-II puncta in the mossy cells of sdy mice. In addition, overexpression of dysbindin-1C, but not 1A, in cultured cells increased LC3-II level and the LC3 puncta in the transfected cells. These results suggest that dysbindin-1C deficiency causes impaired autophagy, which is likely implicated in the pathogenesis of SCZ.